Six months of hybrid closed-loop therapy improves diabetes-specific positive well-being, and reduces diabetes distress and fear of hypoglycemia: secondary analysis of a randomized controlled trial - Anthony C Keech; Vijaya Sundararajan; Bruce R King; Sara Vogrin; Richard J MacIsaac; Leon A Bach; Jane Speight; Alicia J Jenkins; Christel Hendrieckx; David O’Neal; Sybil A McAuley; Geoff R Ambler; et al. (BMJ Open Diabetes Research & Care)
Introduction This analysis aimed to investigate diabetes-specific psychological outcomes among adults with type 1 diabetes (T1D) using hybrid closed-loop (HCL) versus standard therapy.Research design and methods In this multicenter, open-label, randomized, controlled, parallel-group clinical trial, adults with T1D were allocated to 26 weeks of HCL (MiniMed™ 670G) or standard therapy (insulin pump or multiple daily injections without real-time continuous glucose monitoring). Psychological outcomes (awareness and fear of hypoglycemia; and diabetes-specific positive well-being, diabetes distress, diabetes treatment satisfaction, and diabetes-specific quality of life (QoL)) were measured at enrollment, mid-trial and end-trial. Linear mixed models were conducted, using restricted maximum likelihood estimation, unadjusted and adjusted (for covariates: age, sex, diabetes duration, glycated hemoglobin, recent severe hypoglycemia, pre-trial insulin delivery modality, enrollment and mid-study scores).Results 120 participants (mean age 44±12 years) were randomized to intervention (n=61) or standard therapy (n=59). At 13 weeks, the HCL group had better diabetes-specific positive well-being than the standard therapy group (unadjusted: Δ=1.0, p=0.025; adjusted: Δ=1.1, p=0.01), which was maintained at 26 weeks (unadjusted: Δ=0.9, p=0.042; adjusted: Δ=1.0, p=0.023). At 26 weeks, the HCL group also had less diabetes distress (adjusted: Δ=−6.4, p=0.039), fear of hypoglycemia (“maintain high”: adjusted: Δ=−0.8, p=0.034; and “worry”: adjusted: Δ=−1.8, p=0.048), and perceived “unacceptably high glucose levels” (unadjusted: Δ=−1.1, p<0.001; adjusted: Δ=−1.1, p<0.001). HCL did not improve diabetes treatment satisfaction, diabetes-specific QoL, hypoglycemia awareness, or perceived frequency of unacceptably low glucose levels.Conclusions These findings imply that HCL offers important psychological benefits. In particular, improvement in diabetes-specific positive well-being was observed 13 weeks after HCL initiation and maintained at 26 weeks. Reduction in the perceived frequency of hyperglycemia was also apparent by 26 weeks. Adjusted analyses showed significant reductions in diabetes distress and fear of hypoglycemia at 26 weeks, suggesting these benefits were apparent for people with particular characteristics.Trial registration number Australian New Zealand Clinical Trials Registry: ACTRN12617000520336.